Heat and Mass Transfer Study of Top-Heat-Integrated Distillation Column (T-HIDiC) using CFD - Javier A. Mancera-Apolinar; Diego F. Mendoza; Ronnie Andersson; Carlos A. M. Riascos (Chemical Engineering Transactions)
Distillation is one of the most widely used separation techniques in chemical processes, this separation method accounts for a significant portion of global energy consumption. Process intensification strategies have led to alternative technologies such as Heat Integrated Distillation Columns (HIDiC), these units can significantly reduce energy consumption. The goal of this study is to develop a CFD model to analyze momentum, heat and mass transfer in the separation of propylene/propane system in a Top HIDiC. The initial and boundary conditions are based on data from Aspen plus process simulations. Ranz-Marshall approaches are used for the representation of the heat transfer between phases and resistance in the gas phase. The mass transfer coefficient was calculated using Higbie’s model implemented via UDF. The Peng-Robinson thermodynamic equilibrium model was implemented to estimate equilibrium ratio at the interface by UDF. The developed CFD model was used to evaluate three pairs of internal rectification stage plus external stripping stage, that are thermally integrated. These stages were selected as representative of the column. Phases distribution, temperature and vapor phase Murphree efficiency were obtained as results, showing the potential of CFD models to analyze new and structurally complex units.